The banking sector and Islamic banking in the middle eastern and north African countries - (:unkn) unknown (Springer International Publishing, 2014)
The Financial sector has been a priority field for MENA. Financial deficiencies do have an impact both on the funding and materialization of projects and the inability to accumulate savings in countries. Colonial impacts dating back to the nineteenth century were decisive in the development of banking in the MENA. However, the circumstances changed in the twentieth century, when the region started to enrich its banking experiences through different and original practices in ̄slamic banks or other banks. Islamic Banking which has been rapidly emerging in the MENA extends over to Europe and Asia. Yet, the important thing at this point is to enhance the effectiveness of these banks in parallel to their development. The models of Islamic banking which emerged in the banking sector in a modern way did not remain limited to Muslim countries only, but have also grown internationally. Islamic banks mostly operated in the MENA region in the past, but proliferated in the Muslim parts of Asia after the 1980s. This proliferation of Islamic banking was particularly made possible by the fact that Islamic banks continued to operate successfully and holding a greater proportion of liquid assets than other banks made Islamic banks more resilient and successful during the crisis. © Springer International Publishing Switzerland 2014. All rights are reserved.
Keywords: Banking; Crisis; Islamic banking; MENA